An Econometric Time-Series Analysis of the Dynamic Relationship among Trade, Financial Development and Economic Growth in India - Sreenu, Nenavath (Asian Economic and Financial Review, 2019)
The study conducted to investigate the relationship among financial development, international trade and economic growth evolution and also examine the important considerable variables are economic growth, export services, import services, international trade, gross capital formation and exchange rate as independent variables. Further the study is to examine if there is any exists a long run relationship among various financial development, trade growth and macroeconomic variable development in India for the period 2000 to 2018. In this connection, the paper used the Johansen co-integration method, KPSS, ADF and PP to establish the survival of a long run relationship among financial development, economic growth and trade variables and Johansen co-integration approach is used to determine the long run relationship of GDP growth. The outcomes of the paper are that financial development, trade and economic development are co-integrated, but the relationship is supported by the constancy of the macroeconomic policy subsequently undesirable macroeconomic variables such as escalating inflation can constrain economic growth.